The Formal Divide: Customary Rights and the Allocation of Credit to Agriculture in Tanzania. Issue 9 (1st September 2016) - Stein, Howard; Maganga, Faustin P.; Odgaard, Rie; Askew, Kelly; Cunningham, Sam
ABSTRACT: It is generally held that one mechanism to enable inclusive growth in Tanzania is enabling farmers to access credit to raise productivity and incomes. The formalisation of property rights in Tanzania is being undertaken by a multiplicity of actors at great expense to donors, individuals and the government. While there have been a variety of different justifications for allocating Certificates of Customary Rights of Occupancy (CCROs) to farmers in Tanzania, perhaps the most prominent argument is that it will enable farmers to finally overcome the divide between 'informal' customary rights and the formal banking sector. CCROs would provide the collateral that would induce banks to lend money to small-scale farmers. As part of a six-year investigation in Manyara, Mbeya and Dodoma regions, our research team evaluated the impact of formalisation on farmers' access to credit. The paper will present the results while pointing to the continuing institutional and market imperfections that perpetuate the formal divide.